Yield and Gap analysis of Wheat (Triticum aestivum) Productivity in NCR of Delhi - Jitender Kumar , Y. P. Singh and D. K. Rana, (Indian Journal of Extension Education, 2014)
Krishi Vigyan Kendra, Delhi laid out demonstrations for replacement of yellow rust susceptible varieties PBW 343 andWH 711with the high yielding variety (HYV) HD 2967 of wheat with or without seed inoculation with bio-fertilizers viz.Azotobactor and Phosphate Solubilizing Bacteria (PSB) during 2012-13 and 2013-14. Twenty five and twenty fourfarmers were selected randomly for demonstrating the technology during 2012-13 and 2013-14, respectively. The soil ofthe demonstration field was sandy loam, low in nitrogen and medium in phosphorus and potash. The major crop rotationst was pearl millet-wheat and paddy-wheat. The crop was sown in 1 fortnight of November. The average yield andeconomics of demonstration and check plots were calculated. During the year 2012-13 the highest average yield of varietyHD 2967 was observed with bio-fertilizers 59.25 q./ha which was 5.46 per cent and 11.54 per cent more as compared toHD 2967 without bio-fertilizers (56.18q/ha) as compared to local check variety WH 711 (52.52 q/ha) under farmerspractice, respectively. The average net returns of demonstrated plots under HYV HD 2967 with bio-fertilizers was `63179 and ` 58841 under HYV HD 2967 without bio-fertilizers which was 16 per cent and 10.5 per cent, respectively,higher than the local check variety.